A gestão do espaço construído e a prevenção criminal - Rodrigues, Adérito Grazina (2017)
Crime prevention through environmental design it is based on the idea that through the design, use and maintenance of lowering opportunities for the occurrence of crimes and of providing a sense of security to people. Based on four principles (natural surveillance, natural access control, territoriality and maintenance and management) preventive strategies should be geared to the specific space being handled, given the crime problem, insurance and social of it. Urban design influences the crime and can help reduce the opportunities for the occurrence of crimes. It was carried out a case study in the Luísa Todi Avenue in the city of Setúbal , which has undergone rehabilitation works in 2008 under the Polis Programme and later on the initiative of the Municipality of Setúbal. The aim of the study was guided in finding answers to the central question, that is, if the requalification at Luísa Todi Avenue had an impact on street crime. This study aims to contribute to a better understanding of this theory , showing up its effect in practice and to meet the various entities with security responsibilities and administrative in Setúbal , existing vulnerabilities in Luísa Todi Avenue. This research adopted a qualitative research strategy (Bryman, 2012), materialized from desk research and a survey interview, semi-structured, whose data content object of analysis (categorical) supported by Bardin (2000). As regards the research design, we have chosen for the case study, as prepared a detailed and intensive analysis of a single case, making it possible to capture the complexity and the particular nature of the case. It was concluded that the rehabilitation works occurred in 2008 on Luísa Todi Avenue, had a positive impact on reducing street crime, since this phenomenon has shown a decreasing trend, contrary to what happens in the city of Setúbal. The principles of CPTED are applied even if they have not been specifically considered in the redevelopment project.